2018
DOI: 10.1155/2018/1471808
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors and Inequality in the Prevalence and Treatment of Diabetes among Middle-Aged and Elderly Adults in China

Abstract: Background In China, the prevalence of diabetes has increased significantly over recent decades, owing to the county's rapidly aging population. Although many studies have examined the prevalence of diabetes worldwide, there has been little analysis of the inequalities in its prevalence and treatment among middle-aged and elderly people. Objectives This study evaluates influence factors and inequality in respect to the prevalence of diabetes and medication treatment among middle-aged and elderly Chinese adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 30 publications
(43 reference statements)
7
22
2
Order By: Relevance
“…1). A study has demonstrated that the women diabetic awareness rate is higher than in men in rural areas 21 , which is different from the results reported in this study. This difference may be due to the larger urban population that was included in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…1). A study has demonstrated that the women diabetic awareness rate is higher than in men in rural areas 21 , which is different from the results reported in this study. This difference may be due to the larger urban population that was included in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Policies for reducing the inequality of diabetes incidence ought to focus on the socioeconomic factors, such as implementing strategies to enhance hygiene health education, promote healthy lifestyles to control obesity rate, narrow the disparity between urban and rural areas [23].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we defined X k as the socioeconomic factor related to diabetes prevalence. Thus, the linear regression analysis model of diabetes prevalence and related factors is as follows [23]:…”
Section: Decomposition Of the CImentioning
confidence: 99%
“…In this study, we defined as the socioeconomic factor related to diabetes prevalence. Thus, the linear regression analysis model of diabetes prevalence and related factors is as follows [23]:…”
Section: Decomposition Of the Concentration Indexmentioning
confidence: 99%